2015
DOI: 10.1155/2015/436879
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Changes in Endothelial Progenitors as a Possible Cellular Basis for Glycemic Memory in Diabetic Vascular Complications

Abstract: The vascular complications of diabetes significantly impact the quality of life and mortality in diabetic patients. Extensive evidence from various human clinical trials has clearly established that a period of poor glycemic control early in the disease process carries negative consequences, such as an increase in the development and progression of vascular complications that becomes evident many years later. Importantly, intensive glycemic control established later in the disease process cannot reverse or slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 142 publications
(173 reference statements)
2
36
0
1
Order By: Relevance
“…Occurrence of this phenomenon has been reported in endothelial cells, in which it is driven by different mechanisms, such as oxidative stress and epigenetic changes [19]. DDP-4 inhibitors are anti-diabetic agents with vascular protective effects [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Occurrence of this phenomenon has been reported in endothelial cells, in which it is driven by different mechanisms, such as oxidative stress and epigenetic changes [19]. DDP-4 inhibitors are anti-diabetic agents with vascular protective effects [32].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that following a hyperglycemic stress, the levels of basement membrane proteins such as collagen and fibronectin, which are markers of high glucose stress, remain elevated several days after glucose levels have normalized [16,17]. This phenomenon, defined as "metabolic memory", has been linked to poor glycemic control in the early phases of diabetes, despite a tight glycemic control achieved during the course of the disease [18][19][20]. Several preclinical and clinical studies have demonstrated the existence of a metabolic memory in endothelial cells [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 'early' outgrowth cells, selected by short-term culture, are classified as immediately adherent cells of hematopoietic origin expressing CD45, CD14 and CD11b, apart from VEGFR2 (Flk-1). They are able to support vasculogenesis and angiogenesis but are not able to spontaneously form tubules in vitro [Rehman et al, 2003;Hirschi et al, 2008;Yoder, 2012Yoder, , 2013Rajasekar et al, 2015;Recchioni et al, 2016]. The 'early' EPCs contribute to angiogenesis in a paracrine manner by secreting proangiogenic molecules, and are able to incorporate into capillaries in perivascular positions [Hirschi et al, 2008].…”
Section: Defining Circulating and Resident Epcsmentioning
confidence: 99%
“…Importantly, the deregulation of epigenetic features of EPCs plays a key role in DM-induced vascular injury and endothelial dysfunction [11]. DNA methylation / hydroxymethylation / transmethylation, histone modifications, and differential expression of specific non-coding RNAs like microRNA (miRNAs) are discussed as causative mechanisms of epigenetic modifications [12]. Despite this, the early phases of epigenetically changes in EPCs are pre-diabetic situation affected mitochondrial injury upon hyperglycemic insult, oxidative stress activation, and lowering survival ability of cell organelles [13].…”
Section: Editorialmentioning
confidence: 99%